German cities to see further rises in housing prices and rents in 2013 - Konstantin A. Kholodilin; Andreas Mense (DIW Economic Bulletin, 2012)
Over the past few years, prices and rents for flats went up in most German cities. This trend is expected to continue in 2013. Berlin, Hamburg, Munich, and Frankfurt am Main will still see the highest increases in property prices and rents. In these cities, housing prices are rising much faster than rents. By contrast, stagnating or even falling prices are forecast for the cities in the Ruhr area.
Keywords: C21; C23; C53; 330; housing prices; housing rents; forecasting; dynamic panel model; spatial autocorrelation; German cities